THE EFFECTS OF PESTICIDES ON THE HEALTH OF PEASANT COCOA FARMERS IN MUNYENGE, SOUTH WEST CAMEROON - Amambang Arnold Achancho; Divine Nsobinenyui; Martin Mih Tasah; Ndaleh Wozerou Nghonjuyi (Bernas : Jurnal Penelitian Pertanian, 2019)
There is a significant increase in the use of pesticide and these chemicals have potential adverse effects on human health. This study aimed to investigate the effects of exposure to pesticides on the liver, heart and lungs functions of 296 cocoa farmers with more than 1 year experience. One hundred non-farmers were recruited as a control group to compare levels of alanine aminotransferase (ALT) and aspartate aminotransferase (AST). The results indicated that AST and ALT were significantly (P<0.05) increased in pesticide-exposed workers compared withcontrol. However, there was a positive correlation between AST and ALT among exposed group. Increase in chemical applications was positively correlated with increase in the levels of AST and ALT in the blood. Munyenge farmers require more attention on pesticide use so as to limit the health hazards caused by the side effects of these chemicals.